Investigación en la formación de profesores de matemáticas. Agendas y perspectivas - Lurduy O, Jorge O. (Revista Científica, 2011)
This document intends to arrange the developments and the agendas of current investigation in the Mathematical Education, in the subject matter of the mathematics teaching education, particularly the results of the investigation of bibliographical review on one of the topics that in the community of investigators of the mathematical Education is generating greater attention by its recognized and accepted strategic importance as is the concerning to the mathematics professional development teacher education and in it that of the formation of the didactic competences of the professors in exercise and them developed in the mathematics teacher education programs with the students for teacher of mathematics (epm).